2018
DOI: 10.1007/s00167-018-4970-y
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease increases the risk of perioperative complications after total knee arthroplasty: a nationwide database study

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Revision surgery due to mechanical complications tended to be higher, but not signi cantly, in the PD(+) group (revision surgery: 33.3% vs 12.5%, p = 0.086). [24,25]. Furthermore, other surgical studies on the PD population have suggested higher rates of postoperative medical complications such as pneumonia, delirium, and sepsis [5].…”
Section: Resultsmentioning
confidence: 99%
“…Revision surgery due to mechanical complications tended to be higher, but not signi cantly, in the PD(+) group (revision surgery: 33.3% vs 12.5%, p = 0.086). [24,25]. Furthermore, other surgical studies on the PD population have suggested higher rates of postoperative medical complications such as pneumonia, delirium, and sepsis [5].…”
Section: Resultsmentioning
confidence: 99%
“…HY stage was higher in the revision subgroup, although this was not significantly different (2.8 ± 1.2 vs 2.2 ± 1.3, p = 0.29). [18,19]. Furthermore, other surgical studies on the PD population have suggested high rates of postoperative medical complications such as pneumonia, delirium, and sepsis [5].…”
Section: Resultsmentioning
confidence: 99%
“…HY stage was higher in the revision subgroup, although this was not signi cantly different (2.8 ± 1.2 vs 2.2 ± 1.3, p = 0.29). [18,19]. Furthermore, other surgical studies on the PD population have suggested high rates of postoperative medical complications such as pneumonia, delirium, and sepsis [5].…”
Section: Resultsmentioning
confidence: 99%